Quality Ambiguity and the Market Mechanism for Credence Goods - Dietrich Benner (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2004)
With credence goods consumers cannot judge actual quality neither before purchase - ex ante - nor after purchase - ex post -. Trust has to replace own examination and verification. Applying Choquet-Expected Utility theory, a general model of credence goods is developed which takes the problem of trust explicitly in its view and generalizes the problem of quality uncertainty on the ?market for lemons? of Akerlof (1970) to ?quality ambiguity? with credence goods. The model shows the market mechanism only performing well in providing credence goods when consumers? trust in given information is not too low. With trust too low, sellers of credence goods will be driven out of the market by trust induced adverse selection. In market equilibrium prices will always be lower compared to equilibrium prices for experience goods.
urn:nbn:de:bsz:100-opus-801
Keywords: C72; D81; D82; 330; credence goods; asymmetric information; quality ambiguity; uality uncertainty; adverse selection; ambiguity; choquet expected utility; Choquet-Erwartungsnutzentheorie